Implementasi Shalawat Simtud Duror dalam Meningkatkan Kehidupan Spritual Jamaah di Majelis Taklim Berkah Sekumpul Studi kasus hadis - Sabuki, Robi; Damanik, Nurliana (STAIN MAJENE, 2025)
Abstract This study examines the practice of reciting Shalawat Simtudduror and the role of Majelis Taklim Berkah Sekumpul in fostering the spiritual and social development of the community in Lubuk Bayas Village, Serdang Bedagai. Established in 2012 under the leadership of Al-Ustadz Arbanik, the majelis has grown into a center of Islamic learning grounded in an unbroken chain of scholarly transmission (sanad) linked to Banjar ulama and Abah Guru Sekumpul. Using a descriptive qualitative approach through observation and interviews with 17 regular participants, the research reveals that the majelis conducts various religious activities, including the recitation of Simtudduror, study circles on fiqh, creed, and Sufism, as well as religious education for children. The tradition of reciting Simtudduror serves as a powerful spiritual, emotional, and social instrument that cultivates values of mahabbah (love for the Prophet) and tazkiyah al-nafs (purification of the soul). Its poetic and deeply meaningful verses strengthen inner peace, social cohesion, and the internalization of prophetic ethics among the congregation. The study concludes that Majelis Taklim Berkah Sekumpul not only preserves shalawat traditions and scholarly lineage but also functions as a space for spiritual development, moral education, and the reinforcement of the community’s religious identity.